Line Profile Property of Autoionizing States. (July 2015) - Tu, B; Xiao, J; Yao, K; Shen, Y; Yang, Y; Lu, D; Fu, Y Q; Wei, B; Zheng, C; Huang, L Y; Hutton, R; Zou, Y
Synopsis: This work studied the interference effect between dielectronic recombination and radiative recombination of highly charged tungsten ions. Our result shows a coexistence of Fano and Lorentzian line profile of autoionizing states.